The Effectiveness Factors of Student Learning through TikTok Media with the Application of the TAM Model - Florencia Elaine; Ikhsan Fuady (Jurnal Pendidikan Multimedia (Edsence), 2023)
This study aims to examine the factors that have an impact on the learning effectiveness of students who use social media TikTok for learning and gaining knowledge. Extended Technology Acceptance Model (TAM) theory is the main framework used to analyze, with the constructs of perceived ease of use, perceived usefulness, attitude towards TikTok Use, Behavioral intention to use, and learning effectiveness. Questionnaire data collection was carried out by hosting an online Google Form which was distributed to active students on the island of Java using nonprobability method and involving 181 samples. The data obtained was analyzed using LISREL with SEM and confirmatory factor analysis (CFA) to test the validity, reliability, hypothesis testing, and models. The results of the study show that the model has been able to explain the factors of learning effectiveness and the acquisition of new knowledge using TikTok media for university students in Java. In addition, the relationship between behavioral intention to use and learning effectiveness is a prominent and significant construct of this research.